Nanoparticles: A High‐Throughput Automated Confocal Microscopy Platform for Quantitative Phenotyping of Nanoparticle Uptake and Transport in Spheroids (Small 37/2019). Issue 37 (11th September 2019) - Cutrona, Meritxell B.; Simpson, Jeremy C.
Abstract : In article number1902033, Meritxell B. Cutrona and Jeremy C. Simpson describe a high‐throughput automated confocal microscopy platform which allows for the generation of multiple levels of quantitative information with respect to how nanoparticles interact with cells. These interactions can be measured at the subcellular level, cell spheroid level and spheroid population level.